Scarcity Message, FOMO, and Social Persuasive Technology on Impulse Buying among Generation Z Fast Fashion Consumers - Putra Pratama; Elda Sri Andini; Rino Febrianno Boer (Universitas Pendidikan Indonesia, 2025)
Introduction/Main Objectives: This study examines the effect of scarcity message, fear of missing out (FOMO), and social persuasive technology on impulse buying behavior among Generation Z consumers in Indonesia’s fast fashion industry. As digital natives, Generation Z consumers are highly responsive to marketing stimuli and social interactions in digital environments. Background Problems: Despite growing literature on impulse buying behavior, limited studies examine how scarcity message, FOMO, and social persuasive technology jointly influence impulse buying among Generation Z consumers in fast fashion. Novelty: This study integrates these variables into a single empirical model to explain impulse buying behavior among Generation Z consumers, addressing limited research examining these factors together. Research Methods: This study uses a quantitative survey using data from 211 Generation Z consumers who purchased fast fashion products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results: Results show scarcity message, FOMO, and social persuasive technology have positive and significant effects on impulse buying behavior, with social persuasive technology emerging as the strongest predictor. Conclusion: The findings highlight the role of digital-social persuasion in shaping impulse buying among Generation Z and provide theoretical contributions to Marketing 5.0 and implications for fast fashion marketers.